If it's not what You are looking for type in the equation solver your own equation and let us solve it.
15-9(2x+3)=-16x+40
We move all terms to the left:
15-9(2x+3)-(-16x+40)=0
We multiply parentheses
-18x-(-16x+40)-27+15=0
We get rid of parentheses
-18x+16x-40-27+15=0
We add all the numbers together, and all the variables
-2x-52=0
We move all terms containing x to the left, all other terms to the right
-2x=52
x=52/-2
x=-26
| 3(x-2)=2x-4+x-1 | | 10y+19.95=139.96 | | 2^x+2+2^x+1=9 | | X/3+6=x/9-10 | | 12x+10=5-6x | | -25-10r=5(-6+2r) | | 4x2-12=4x2+2x-7 | | 84=-12+b | | 12x+14-3x+7=7(x+3)+2x | | 6x²+15x+135=0 | | -7+4(c+8)=-2(c-1) | | 3(x-1)+4x=4 | | x-2(1/4)(x-1/2)=1/6(2x+1)+1/3 | | 7y+-4y=-18 | | 8+.4x=4+.6x | | 11–5a=51 | | 6x-20=-14x+4 | | 3^2+10x–117=0 | | 5x-7=4x-1= | | 1-5x/8=3 | | 350+50x=800 | | 27-15=2(x-3)= | | 1.4t(t-3.1)=5.8 | | 5x2x2=10x5 | | 24=8x-4(x-8) | | 7g=9g−2g | | 12=10+x/5 | | 1.06g+-3=0.71 | | 5x+23+4x+31=180 | | x/8-x/9=9/8 | | 4a=3+11 | | 6x+30x-22x=392 |